2023
DOI: 10.1002/advs.202300988
|View full text |Cite
|
Sign up to set email alerts
|

Rescuing Nucleus Pulposus Cells From Senescence via Dual‐Functional Greigite Nanozyme to Alleviate Intervertebral Disc Degeneration

Abstract: High levels of reactive oxygen species (ROS) lead to progressive deterioration of mitochondrial function, resulting in tissue degeneration. In this study, ROS accumulation induced nucleus pulposus cells (NPCs) senescence is observed in degenerative human and rat intervertebral disc, suggesting senescence as a new therapeutic target to reverse intervertebral disc degeneration (IVDD). By targeting this, dual‐functional greigite nanozyme is successfully constructed, which shows the ability to release abundant pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…The hydrogel improved the metabolism of the NPCs matrix, which was conducive to the long-term treatment of IDD. In addition, more and more research has shown that abnormal intracellular reactive oxygen species (ROS) levels are associated with NPSCs aging and are also a significant cause of IDD [122][123][124]. IDD can be slowed down by controlling the source ROS levels.…”
Section: Intervertebral Disc Degenerationmentioning
confidence: 99%
“…The hydrogel improved the metabolism of the NPCs matrix, which was conducive to the long-term treatment of IDD. In addition, more and more research has shown that abnormal intracellular reactive oxygen species (ROS) levels are associated with NPSCs aging and are also a significant cause of IDD [122][123][124]. IDD can be slowed down by controlling the source ROS levels.…”
Section: Intervertebral Disc Degenerationmentioning
confidence: 99%